A Case Report of Myxedema Megacolon Required Sigmoidectomy - Osada, Akira; Ozaki, Azusa; Iwasaki, Yoji; Adachi, Shinya; Watanabe, Muneaki (Nippon Shokaki Geka Gakkai zasshi, 1990)
A 62-year-old male was admitted to the hospital with acute abdominal pain. X-ray films of the abdomen showed ileus due to sigma volvulus, and he underwent a repairing operation. After surgery, myxedematous skin appeared on his extremities, and thyroidal examination revealed the patient had had marked hypothyroidism with myxedema megacolon. For three months after the surgery he received thyroid hormone treatment, but paresis of the large intestine worsened. Accordingly, the sigmoid colon was resected. Histological examination revealed marked deposits of myxedematous material in the submucosa layer and the internal circurating muscles. He was discharged from the hospital and is living well with treatment with levothyroxine sodium.